Do technological innovation, financial development, education, and institutional quality contribute to environmental sustainability? Evidence from COSTA RICA - Hechmi, Soumaya; Chaabouni, Ines (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores how technological innovation, financial development, education, and institutional quality impact CO₂ emissions between 1995 and 2021 in Costa Rica, one of the developing nations that have found ways to balance economic development with sustainable measures. We apply the Autoregressive Distributed Lag (ARDL) model and the Error Correction Model (ECM) to analyze the short-run and long-run relationships between the variables. Time-series data are analyzed to determine the direction and magnitude of these relationships. The results indicate that financial development positively correlates with CO₂ emissions in the long run, while technological innovation reduces environmental degradation. Short-run results show that institutional quality initially worsens emissions, while financial development and education contribute to mitigating CO₂ emissions. The findings underscore the need for policy aimed at balancing financial growth and environmental responsibility. Institutional quality and technological progress are central to achieving long-run sustainability. Policymakers ought to prioritize the implementation of sustainable investment methodologies, augment institutional frameworks, and advocate for innovation-oriented environmental policies. The adoption of these measures will be crucial for the mitigation of CO₂ emissions while concurrently facilitating sustained economic advancement.